Pengaruh Return On Asset (ROA) dan Earning Per Share (EPS) Terhadap Harga Saham pada Bank BUMN yang Terdaftar di Bursa Efek Indonesia - Nyayu Khairani Putri; Sasiska Rani (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study aims to determine the effect of Return On Asset (ROA), Return On Equity (ROE), and Earning Per Share (EPS) on Stock Prices at BUMN Banks Listed in BEI. The analysis technique in this research is descriptive method. The population used in this study is BUMN Banks listed on the IDX with a time period of six (6) years, namely 2017-2022. the number of research samples is six (6) companies and uses a sampling method, namely the saturated sample method on the grounds that the population is less than 50. The results showed that partially Return On Asset (ROA) and Earning Per Share (EPS) had a significant effect on Stock Prices at BUMN Banks listed on the IDX. Then simultaneously Return On Asset (ROA) and Earning Per Share (EPS) have a significant effect on Stock Prices at BUMN Banks listed on the IDX.